Peningkatan Kapasitas Mahasiswa dalam Penggunaan Software Pengolahan Data Berbentuk Dokumen melalui Pelatihan Microsoft Office - Yanna, Sri; Ristawati, Ristawati; Mirza, Mirza; Fajri, Riyadhul; Iqbal, Iqbal; Sriwinar, Sriwinar (Aceh Journal of Community Engagement (AJCE), 2023)
Community service activities in the form of providing training to 20 students, 25 November 2023 at the Computer Laboratory of the Indonesian National Islamic University (UNIKI) Bireuen, Aceh province. With the aim and objective of increasing students' capacity in processing documents digitally, using Microsoft Office 2022. This activity involves counseling about the substance of the activity, followed by a demonstration in operating Microsoft Office, especially Word, Excel and Powerpoint. Tests are also carried out to test or measure the extent to which the training participants absorb the training material that has been provided. Apart from direct practice in creating documents, the participants were given direction on office concepts and good displays such as choosing fonts, paragraphs, sizes and letters. Based on the results of the training, it can be seen that the participants were quickly and effectively able to understand and use the tools. –tool in office, can cut and move images, add, arrange text, and organize images.